Investigating Degradation in Extrusion-Processed Bio-Based Composites Enhanced with Clay Nanofillers - Tara, Ahmed; Bencharki, Mouhja; Gainvors-Claisse, Angélique; Berzin, Françoise; Jbara, Omar; Rondot, Sébastien (Biomass, 2024)
This research investigates the extrusion-based fabrication and characterization of nanocomposites derived from bio-sourced polypropylene (PP) and poly(butylene succinate) (PBS: a biodegradable polymer derived from renewable biomass sources such as corn or sugarcane), incorporating Cloisite 20 (C20) clay nanofillers, with a specific focus on their suitability for electrical insulation applications. The research includes biodegradation tests employing the fungus Phanerochaete chrysosporium to evaluate the impact of composition and extrusion conditions. These tests yield satisfactory results, revealing a progressive disappearance of the PBS phase, as corroborated by scanning electron microscopy (SEM) observations and a reduction in the intensity of Fourier transform infrared spectroscopy (FTIR) peaks associated with C-OH and C-O-C bonds in PBS. Despite positive effects on various properties (i.e., barrier, thermal, electrical, and mechanical properties, etc.), a high clay content (5 wt%) does not seem to enhance biodegradability significantly, highlighting the specific sensitivity of the PBS phase to the addition of clay during this process. This study provides valuable insights into the complex interplay of factors conditioning nanocomposite biodegradation processes and highlights the need for an integrated approach to understanding these processes. This is the first time that research has focused on studying the degradation of nanocomposites for electrical insulation, utilizing partially bio-sourced materials that contain PBS.
Number: 3
Keywords: biocomposites; degradability; extrusion; materials properties; nanoclay; polymers